Modulation of GABAB receptors in the insula bidirectionally affects associative memory of epilectic rats in both spatial and non-spatial operant tasks - Wu, Nan; Sun, Tao; Wu, Xin; Chen, Hongguang; Zhang, Zhen (Frontiers in Behavioral Neuroscience, 2023)
Background Stimulation of gamma-aminobutyric acid (GABA) activity through GABA receptor agonists is the basic mechanism of many anticonvulsant drugs. Nevertheless, many of these GABergic drugs have adverse cognitive effects. We previously found that GABAB receptors (GABABRs) in the insula regulate operant associative memory in healthy rats. The present study aimed at investigating the effects of GABABR modulation in the insula on operant associative memory in epileptic rats, along with the underlying mechanisms. Methods The lithium-pilocarpine model of temporal lobe epilepsy (TLE) was established in male Sprague–Dawley rats. A 22-gauge stainless-steel guide cannula was surgically implanted into the granular insula cortex of the epileptic rats. Baclofen (125 ng/μl, 1 μl), CGP35348 (12.5 μg/μl, 1 μl), or saline (1 μl) was slowly infused through the guide cannula. The Intellicage automated behavioral testing system was used to evaluate operant associative memory of the epileptic rats, including non-spatial operant tasks (basic nosepoke learning and skilled nosepoke learning) and spatial operant tasks (chamber position learning). The expression of the GABABR subunits GB1 and GB2 in the insula was examined by immunofluorescence and Western blotting. Results The Intellicage tests demonstrated that baclofen significantly impaired basic nosepoke learning, skilled nosepoke learning and chamber position learning of the epileptic rats, while CGP35348 boosted these functions. Immunofluorescence staining revealed that GB1 and GB2 were expressed in the insula of the epileptic rats, and Western blotting analysis showed that baclofen enhanced while CGP35348 inhibited the expression of these subunits. Conclusion GABABRs in the insula bidirectionally regulate both spatial and non-spatial operant associative memory of epileptic rats. Effects of GABABRs on cognition should be taken into account when evaluating new possible treatments for people with epilepsy.